NIVEL DE ACEPTACIÓN Y PERCEPCIÓN DE LOS PADRES FRENTE AL TRATAMIENTO CON FLÚOR DIAMINO DE PLATA EN UN COLEGIO PERUANO. UN ESTUDIO TRANSVERSAL - Cruz-Flores, María Elizabeth (2025)
Objective: To evaluate the level of acceptance and perception of parents regarding treatment with silver diamine fluoride (SDF). Materials and Methods: Descriptive, quantitative, cross-sectional, and prospective study conducted with 124 preschool parents, selected through cluster sampling. A validated survey was used, with a Cronbach's alpha of 0.970 for acceptability and 0.952 for perception. Chi-square was applied for associations (p < 0.05). Results: 65.32% of parents did not accept the application of SDF on anterior teeth, and 66.13% on posterior teeth. However, overall perception was favorable for anterior teeth (71.77%) and posterior teeth (77.5%). No statistically significant differences were found between anterior and posterior teeth in terms of acceptance or perception. Additionally, education levels showed a significant association with acceptance. Conclusion: Although parent perception was favorable, the acceptability of SDF was low, primarily due to its aesthetic impact. Education levels influenced the acceptance decision.